Музыка. Жизнь и любовь моя: [о творчестве Г. М. Корепанова-Камского] / Г. Корепанов-Камский - Корепанов-Камский Геннадий Михайлович (2011)
Экземпляры: КР (20181210) / Инвентарный номер: МН2624 / Сис.шифр: 85.313(2) / Авт.знак: К 66 / ГРНТИ: 18.41 / ББК: 85.313(2Р)